Tradittonal heritage of the Serbs from Kosovo and Metohija in the prose of Janićije Popović - Pitulić Valentina D. (Zbornik Radova Filozofskog Fakulteta u Prištini, 2013)
In his prose works, Janićije Popović presented the ethno-psychological heritage of the Serbs in Kosovo and Metohija under the Turkish rule. The author, born in Gračanica, was educated in Bitolj, where his teacher, Milan Gajić, was the first to notice his talent for writing. He recorded the social and historical situation in the Old Serbia, under the Turkish rule. His prose works cover the period between 1812 and 1912. In view of the constant Turkish oppression of the Serbian population in this territory and the so-called 'rayah mentality' which, according to Jovan Cvijić, was formed in these peculiar living conditions, the paper is concerned with the forms of the traditional heritage preserving the archetypal patterns of the ancestors. The writings of Janićije Popović depict the customs of the people from Kosovo, particularly the weddings, Family Saint's Day, folk gatherings, as well as architecture, style of clothing and other forms of everyday life. Janićije Popović provided valuable information on the life of the Serbs under the Turkish rule on the eve of the Balkan wars. The importance of the traditional heritage for preservation of the identity is particularly seen in the forms of collective consciousness which are the subject of our study.